Low Prevalence of and Related Factors for Myopia in Primary School Children in North Maluku: Poster Presentation - Observational Study - General practitioner - Sayyidati Rokhimah (Majalah Oftalmologi Indonesia, 2023)
Introduction & Objectives : Myopia is a refractive error that commonly occurs in children, and its onset usually begins during school age. Factors associated with myopia development include genetic and environmental factors. This study aims to investigate the prevalence of myopia and related factors associated with its development in primary school children in the North Wasile District, one of the most remote areas in North Maluku Province, Indonesia. Methods : A cross-sectional study was conducted from May to September 2022 in 8 primary schools in North Wasile. Children's visual acuity was examined using a Snellen or E chart, and an anterior segment examination was also performed. A questionnaire was completed by the parents of the children. Results : A total of 431 primary school children with an age range of 6–13 years and a mean age of 9.4 years participated in the study. Myopia was found in only four children (0.9%), and it was categorized as mild myopia. Among the school children, the majority had non-myopic parents (84.7%), had never watched television (54.1%), had never used mobile phones (37.6%), and spent more than 3 hours per day engaged in outdoor activities (97.7%). Conclusion : The prevalence of myopia is relatively low in primary school children in North Wasile, North Maluku. Having non-myopic parents, spending less time on near work, and spending more time engaged in outdoor activities appear to have a protective effect against myopia.